New Rat Model of Pneumocystis Pneumonia Induced by Anti-CD4(+) T-Lymphocyte Antibodies - Thullen, Timothy D. (American Society for Microbiology, 2003)
The CD4(+) T lymphocyte plays a central role in host defense against Pneumocystis pneumonia but has received only limited attention in rats. CD4(+) T-cell-depleting (OX-38) and nondepleting (W3/25) monoclonal antibodies, which recognize an identical or adjacent epitope, were administered for up to 14 weeks to Lewis rats that had been exposed to Pneumocystis. While OX-38 produced a greater decrease in circulating CD4(+) cells than W3/25, both antibody treatments resulted in similar effects on the health of the rats and the levels of Pneumocystis pneumonia, which were milder than those found with corticosteroids. W3/25 also did not enhance the severity of Pneumocystis pneumonia achieved with corticosteroids alone. We conclude that CD4(+) cell function is more important than CD4(+) cell number in host defense against Pneumocystis in the rat and that this new model permits study of opportunistic infections in the rat without the confounding effects of corticosteroids.